2014
DOI: 10.1088/0964-1726/23/9/095025
|View full text |Cite
|
Sign up to set email alerts
|

Identification and control of a trilayer conjugated polymer actuator

Abstract: This paper presents the effect of three uncertain parameters on a recent model of conjugated polymer actuators and implements a robust controller based on the model developed for this actuator. These uncertain parameters are the diffusion coefficient (D), the charge capacitance (C d ) and the charge-to-strain ratio (α), which are difficult to measure directly. The parameter estimation method used in this article is based on a Bayesian cost function, and gives us an insight on how much the estimation can be tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…63 Moreover, Wang, Alici, and Tan (2014) established a hysteresis 64 model for CPAs and controlled the tip displacement of a CPA using 65 inverse feedforward control. Blanchard and Nguyen (2014) tions such as robot manipulators (Sharma, Rana, & Kumar, 2014), 93 power electronics (Calderón, Vinagre, & Feliu, 2006), drive systems 94 (Xue, Zhao, & Chen, 2006) and process control ( (Podlubny, 1999). A fractional order PID controller whose common 178 form is PI k D l , is defined as The CPA used in this study is shown in Fig.…”
mentioning
confidence: 99%
“…63 Moreover, Wang, Alici, and Tan (2014) established a hysteresis 64 model for CPAs and controlled the tip displacement of a CPA using 65 inverse feedforward control. Blanchard and Nguyen (2014) tions such as robot manipulators (Sharma, Rana, & Kumar, 2014), 93 power electronics (Calderón, Vinagre, & Feliu, 2006), drive systems 94 (Xue, Zhao, & Chen, 2006) and process control ( (Podlubny, 1999). A fractional order PID controller whose common 178 form is PI k D l , is defined as The CPA used in this study is shown in Fig.…”
mentioning
confidence: 99%